VaKE(Values and Knowledge Education). Piloting a strategy for NursingEducation - Pinto, Rosário (2017)
Nurses are expected to have health responses which imply interdisciplinary, multi-professional dynamics, require high responsibility and consistent general knowledge to deal with many different, very specific patient needs, which lead them to deal with situations often triggering dilemmasthat involve moral dimensions. Although it is accepted that nursing is a moral activity and that ethical reflection requires practitioners to think critically about their values and to ensure that these values are integrated into caring in every interaction(1), the focus of teaching is more centered on knowledge (about responsibilities, Code of Ethics, …). In fact, personal values are accepted as inherent to human life, seen as attitudes, beliefs and priorities that bind individuals together and guide behavior(2), and some authors acknowledge that personal values can influence the nurses’ professional behavior(3,4). Academic professors of graduation nurses need to take into account all these dimensions, inasmuch as higher education must maintain dynamics of permanent relevance and adequationto society needs and to the quality control of this offer(5)and these must not be dealt with independently but in relation with each other. Awareness of the importance of a reflected and discussed process that enables rationalization of personal and professional values within the process of care, was the motivation to adhere to a proposal of piloting VaKE methodology within Nursing Academic framework.